Synthesis and Determination of Antibacterial Activity of Jacaranone and Synthetic Analogs - Arias Echandi, María Laura (2017)
Natural product jacaranone, 1, and five more analog derivatives were synthesized and its antibacterial activity against Gram-positive and Gram-negative microorganisms was tested. One of these derivatives, 5, was more active than the natural product, and exhibited a bactericidal effect against Gram-positive and Gram-negative bacteria.